ETIKA BERKOMUNIKASI DALAM AL-QUR’AN ANALISIS PENAFSIRAN HASBI ASH-SHIDDIEQI DALAM TAFSIR AN-NUR - A. M. Ismatulloh (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
For Muslims, al-Qur’an is considered a book of guidance for humankind to navigate every aspect of their life in the world including communication as one of the most important aspects of human life. Because communication is very important for humankind, Islam provides guidelines on how to conduct such activity according to the Qur’an and the Hadith. The Qur’an contains many verses using the term “qaul”, a type of adjectives that can be addressed as general guidelines since such adjectives usually refer to the notion of the ethics of communication. Those Qur’anic verses using the term “qaul” are qaulan ma’rufa, qaulan karima, qaulan layyina, qaulan baligha, and qaulan sadida. According to Hasby ash-Shiddieqi, Islamic ethic of communication involves guidelines on how to convey a message in a way that its wording is concise, clear, and free from negative intention to harm others. Such messages must also comply with the general norms that they must be educative and effective to the audience. Hence, such messages should use attractive words in order to have positive impact on the mind of the audience. Keywords: Ethics of communication, Qur’anic communication, Qur’anic exegesis.